An Optimal Panoramic Strategy for Women safety using IoT - Parveen begum, Afiya; sankeyala, Satynarayana; k., Bhagavan (International Journal of Engineering and Technology, 2018)
This paper provides you an idea about Internet of Things and reviews the origin of IoT, key enabling technologies, IoT architecture, IoT in industrial areas, applications of IoT, Operating system used in IoT devices. As the Internet of Things(IoT) at large will foster billions of devices, people and services to interconnect and exchange information and useful data. We have proposed a real-time application device of IoT useful for women safety in today’s world. Considering the issues increasing on women atrocities, the Universal key question raising in every girl’s mind is when they will have a freedom to walk freely in the society even in odd hours without worrying about their security. This paper will help you to use technology with a new perspective for women safety and to provide proof-based evidence against the perpetrators of crime against women. Every Day women around the world are Harassed, Raped, and Killed. The change in society should come and leads to the time when media broadcast more of women successes rather than harassment. Since we can't respond pertinently in perilous situations, we need a device which automatically senses and saves the victim is one of the idea of this paper.